Muriel Spark and self-help - MacKay, M (Routledge, 2018)
Muriel Spark’s novels are full of characters who offer advice to live by – advice both good and bad. Focusing particularly on her fiction about girls and women, this essay reads this career-long feature of Spark's writing in relation to the mid-century publishing phenomenon of the self-help bestseller. It has been a truism at least since Walter Benjamin’s ‘The Storyteller’ that the modern novel has no wisdom to share with its readers, but this essay argues that both Spark’s narrative concern with mentorship and her stylistic recourse to the aphoristic mode reopen in a distinctive way the question of what secular truths the novel as a form can convey.